Leitura e análise das interferências físicas na arquitetura dos edifícios para a educação superior: o caso da UFC - Campelo, Magda (2005)
This article makes a reflection on the recent process of physical intervention on the architectural set of Universidade Federal do Ceará, focusing on one building typology, representative of modern campus architecture, designed and built in the sixties and seventies. It examines and analyzes these architectural and construction interferences which, since 1990, has gradually and systematically promoted a mutation process of essential values of the buildings and of the campus as an architectural set, through reforms and building expansions. It brings into context, on one side, the moment of consolidation of the University as an institution as influenced by the University Reform of 1968 and, on the other side, the introduction of modern architecture in the State of Ceará. Both facts are structural elements in the spatial configuration of buildings at Universidade Federal do Ceará. The article also highlights the original project of one of the typologies of university buildings within this production phase by selecting ten examples for surveying and studying its aesthetical/formal aspects, based on the methodology proposed by Clark and Pause (1984). Conclusions lead to reflection about criteria adopted in projects of intervention with such characteristics, orienting for projects of university buildings.